Homeroom Management in Shaping The Character Of Students At SD IT Diana As-Saffa Islamic - Niswatul Khaira; Almuhajir; Darmadi (Institut Agama Islam Tribakti Kediri, 2023)
The purpose of this research is to explain the planning, implementation, and supervision of the homeroom teacher in shaping the character of students at SD IT Diana As-Saffa Islamic. This study used a descriptive method and analyzed with a qualitative approach. The sampling technique in this study used purposive sampling, while the data collection technique used observation, interviews and documentation. The research instrument used as a guide for interviews, observation, and documentation is a check list sheet. As for data analysis techniques using the Miles and Huberman models, then the validity of the data uses triangulation techniques. The research results show that. (1) Planning for the homeroom teacher in shaping the character of students at SD IT Diana As-Saffa Islamic consists of 4 stages, namely determining what must be done, setting goals, gathering and analyzing information, and developing alternatives. (2) The implementation of the homeroom teacher in shaping the character of students at SD IT Diana As-Saffa Islamic consists of 4 stages, namely knowing the nature of students, helping to develop good character, supervising at all times, and providing guidance and motivation. (3) Supervision of the homeroom teacher in shaping the character of students at SD IT Diana As-Saffa Islamic consists of 4 stages, namely setting implementation standards, measuring actual per-formance, measuring real implementation and comparing it, and taking corrections. [Tujuan penelitian ini adalah untuk menjelaskan perencanaan, pelaksanaan, dan pengawasan wali kelas dalam membentuk karakter peserta didik di SD IT Diana As-Saffa Islamic. Penelitian ini menggunakan metode deskriptif dan dianalisa dengan pendekatan kualitatif. Teknik pengambilan sampel pada penelitian ini menggunakan purposive sampling, sedangkan teknik pengumpulan data menggunakan metode observasi, wawancara, dan dokumentasi. Instrumen penelitian yang digunakan sebagai pedoman wawancara, observasi, dan dokumentasi adalah lembaran check list. Adapun untuk teknik analisis data menggunakan model Miles dan Huberman, kemudian keabsahan data menggunakan teknik triangulasi. Hasil penelitian menunjukkan bahwa. (1) Perencanaan wali kelas dalam membentuk karakter peserta didik di SD IT Diana As-Saffa Islamic terdiri dari 4 tahapan, yaitu menetapkan apa yang harus dikerjakan, membatasi sasaran, mengumpulkan dan menganalisis informasi, serta mengembangkan alternatif. (2) Pelaksanaan wali kelas dalam membentuk karakter peserta didik di SD IT Diana As-Saffa Islamic terdiri dari 4 tahapan, yaitu mengetahui pembawaan dari peserta didik, membantu mengembangkan pembawaan yang baik, pengawasan setiap waktu, dan memberikan pembinaan dan motivasi. (3) Pengawasan wali kelas dalam membentuk karakter peserta didik di SD IT Diana As-Saffa Islamic terdiri dari 4 tahapan, yaitu menetapkan standar pelaksanaan, mengukur peforma aktual, pengukuran pelaksanaan nyata serta membandingkannya, dan pengambilan koreksi]